Study to determine the knowledge attitudes and practices in relation to some aspects of pregnancy and maternal care among husbands. - Yakandawala, Y.L.H (My University, 1992)
The study review that the attitudes towards maternal care family planning among husbands were favourable. But their knowledge about above subjects was poor. It was noted that the knowledge of husbands in rural sector were poor that the urban sector, in most of the factors considered in the study. As such their behaviours related to maternal care and family planning will not be appropriate. Lack of proper sources of information was the main cause of poor knowledge. It was highlighted that firends were the main source of information. But there desire is to get information from mass media, health personnel, and books. Those husbands also suggested that reproductive health should be included in to the school curriculam as a subject.